Moderating Role of Student Engagement in the Relationship Between Teaching Quality and Academic Performance - Ani, Fitri; Rahardjo, Mudjia; Hasbullah, Hasbullah; Onia, Saifaldin Idris (JURNAL AL-TANZIM, 2025)
This study examines the influence of teaching quality, campus facilities, and student engagement on academic performance and the moderating role of student engagement in the relationship. Data were collected through a survey of 185 students and analyzed using PLS-SEM. The results showed that teaching quality and student engagement positively and significantly influenced academic performance, while campus facilities did not have a considerable effect. Student engagement did not moderate the relationship between teaching quality and campus facilities on academic performance. This model explained 68.4% of the variation in academic performance and had good prediction. These findings emphasize the importance of teaching quality and student engagement to improve academic performance, while campus facilities have limited influence. The practical implication of this study is the importance of focusing on improving teaching quality and student engagement to improve academic performance. Educational institutions are advised to implement interactive and project-based learning. Although campus facilities are essential, their influence on academic performance is limited.